Control of Magnetism in Dilute Magnetic Semiconductor (Ga,Mn)As Films by Surface Decoration of Molecules - Wang, Hailong; Wang, Xiaolei; Xiong, Peng; Zhao, Jianhua (Frontiers in Physics, 2016)
The responses of magnetic moments to external stimuli such as magnetic-field, heat, light and electric-field have been utilized to manipulate the magnetism in magnetic semiconductors, with many of the novel ideas applied even to ferromagnetic metals. Here, we review a new experimental development on the control of magnetism in (Ga,Mn)As thin films by surface decoration of organic molecules: Molecules deposited on the surface of (Ga,Mn)As thin films are shown to be capable of significantly modulating their saturation magnetization and Curie temperature. These phenomena are shown to originate from the carrier-mediated ferromagnetism in (Ga,Mn)As and the surface molecules acting as acceptors or donors depending on their highest occupied molecular orbitals, resembling the charge transfer mechanism in a pn junction in which the equilibrium state is reached on the alignment of Fermi levels.